The Exponentiated of Modifying Hyperbolic Tangent Distribution: Model, Properties, and Applications - Kafi, Rahmat Al; Paksaranuwat, Pawat; Pattarapanitchai, Parichart (Journal of the Indonesian Mathematical Society, 2025)
This article introduces a new two-parameter continuous probability distribution, namely, the Exponentiated of Modifying Hyperbolic Tangent (EMHT) distribution. It is derived by modifying hyperbolic tangent function. Several probability functions and distributional quantities of the EMHT distribution are derived. Maximum likelihood estimation is assigned to find estimators of the EMHT distribution's parameters. Numerical experiments are then conducted to examine the performance of the proposed estimator. The results show that the average estimate for each parameter approaches its actual value as the sample size increases. The final section of this article presents applications of the EMHT distribution to real datasets and performs a comparative study with some existing distributions to exhibit its potential as an alternative model for non-negative continuous data.